PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI UD HENNY ALUMINIUM TELUKDALAM KABUPATEN NIAS SELATAN - Duha, Herna Wati Putri (Universitas Nias Raya, 2024)
The scope of this research is a study of the influence of price on purchasing decisions for UD products. Henny Aluminum Telukdalam South Nias Regency. The purpose of this research is to determine the effect of price on purchasing decisions for UD products. Henny Aluminum Telukdalam South Nias Regency. The analytical method used is simple regression analysis. This type of research is quantitative and associative by distributing questionnaires to UD consumers. Henny Aluminum Teluk in South Nias Regency. With an incidental sampling technique, the sample size was thirty-three respondents. The questionnaire was tested for validity and reliability before collecting data. The results of this research show that price influences purchasing decisions for UD products. Henny Aluminum Teluk in South Nias Regency has a significant influence. This can be proven in the results of the hypothesis test analysis where tcount > ttable. Suggestions put forward to improve product purchasing decisions at UD. Henny Aluminum Teluk in South Nias Regency means that business actors should pay attention to the affordability of consumers in purchasing the products they sell.